Architecture - Marini-Jeanneret, Pascale (5 Continents, 2015)
Architecture, the second Art Brut Biennale, presents a selection of works from the Art Brut Collection (Lausanne), linked together by a common theme. The exhibition and the catalogue show the public new works by perhaps lesser-known authors, while taking a new slant on some historical pieces. Running the gamut from reality to utopia, Art Brut authors design architectures in resonance with their everyday lives or their memories, reorganising the space around them according to their own rules and needs. Their imagination and inventiveness carries them to distant, unexplored lands. Yet the vision of architecture that these Art Brut authors offer us here opens up a new dimension, escaping all practical considerations. Over 250 works by 52 creators of all origins - European, North American, or Asian - have been selected for the exhibition. This book presents colour illustrations, a short biography, and a bibliography for each artist